PREVALENSI STRONGYLOSIS PADA KUDA DI PANTAI PARANGTRITIS - , RIA HARDIANA, Dr. drh. Widagdo Sri Nugroho, M.P. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Many horses at Parangtritis have been used as recreation for tourist facility to enjoy the beach. In the other side, some disease happened in horses include strongylosis. Strongylosis is disease caused by strongyl worm it had impact to economic lost for farmer. The aims of this study were to infestigate the prevalenc and risk factors of stongylosis in horses in Parangtritis. Feces speciments were taken from 80 horses around Parangtritis beach belong to 66 farmers. The feceses were the examined by flotation method in Parasitology Laboratory in Veterinary Medicine Faculty, Universitas Gadjah Mada. The data were analysed descriptively and Chi Square (ÏÂ²) and Odd Ratio (OR) to measured the association of risk factors. lavel The prevalence of stongylosis on the farm 27,3 % and in horses level was 27,5 %. Deworming was associated with strongylosis, it reduced the strongylosis.